The expression of TRPV6 and PMCA1 in the mid-secretory endometrium of infertile patients with unexplained infertility and endometriosis - Metin, Tuba Oezcan; Yilmaz, Nafiye; Yilmaz, Banu Coskun; Yilmaz, Sakir Necat; Erdal, Mehmet Emin; Kavuran, Ilay Buran; Doganer, Adem (Cukurova Univ, Fac Medicine, 2023)
Purpose: The goal of this study was to evaluate the expression of transient receptor potential vanilloid 6 (TRPV6) and plasma membrane Ca2+ ATPase 1 (PMCA1) in the endometrium of infertile women with unexplained infertility (UI) and endometriosis (E), and to compare the findings to healthy fertile women. Materials and Methods: Endometrial expression of TRPV6 and PMCA1 proteins was evaluated during the mid-secretory phase using the immunohistochemical method, and mRNA levels were measured by real-time PCR. Calcium concentrations were determined using Inductively coupled plasma-mass spectrometry (ICP-MS). Results: TRPV6 and PMCA1 protein expression were significantly increased in both luminal and glandular epithelium of UI or E groups compared to the control group. TRPV6 mRNA expression levels were significantly lower in the UI group (0.525 +/- 0.087) compared to the control group (0.809 +/- 0.073). There was no significant difference in PMCA1 mRNA expression levels between the groups. Calcium concentration was significantly higher in women with UI (median (Q1-Q3): 50.57 [40.67-51.37], compared to the control group (median (Q1-Q3): 24.29 [20.11-25.55]). Conclusion: The present findings demonstrate altered expressions of TRPV6 and PMCA1 mRNA and protein, along with differences in calcium concentration among patients, especially those with the UI during the window of implantation. These differences might potentially be considered as one of the underlying causes of infertility. Further studies are needed to elucidate the functional roles of these channels and to develop new strategies for pharmaceutical intervention in the treatment of infertility.
Keywords: Calcium metabolism; endometriosis; TRPV6; PMCA1; unexplained infertility